The Motel Entrepreneur and The Motel Manager - Litzinger, William D. (Academy of Management Journal, 1965)
The article presents a comparative analysis of managers and entrepreneurs. The article defines entrepreneurs as those who are goal and action-oriented, and managers who carry out policies and procedures in order to meet these goals. The roles of independent motel owners and chain motel managers are used to explore the difference, focusing the study on motels in northern Arizona. The article defines the motel industry, outlines the selected personality variables, discusses the risk preference, presents the research methodology, proposes a series of hypotheses and measures, and analyzes the findings.